Single-layer particle pole piece, preparation method thereof and lithium ion battery
By coating the primer slurry on the current collector and spreading active particles, the problems of sedimentation and proportion deviation of active particles are solved, and the uniform distribution of single-layer particle electrodes and accurate characterization of electrochemical properties are achieved, and the rate performance and cycle stability of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202510113437.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-06
AI Technical Summary
In the existing single-layer particle electrode preparation methods, active particles are prone to settle or deviate from the actual battery ratio, making it difficult to accurately obtain electrochemical performance parameters.
By applying the primer slurry on the current collector and spreading active particles thereon, the adhesion of the slurry and the particle surface density of the slurry are adjusted to achieve uniform distribution of the active particles and accurate characterization of the electrochemical properties by controlling the ratio and addition amount of the first solvent and the second solvent.
The uniform dispersion of single layers of active particles of different sizes on the surface of the electrode sheet is achieved, accurate and comprehensive electrochemical data is obtained, and the rate performance and cycle stability of the battery are improved. The operation steps are simple and there is no need to use precision and complex instruments.
Smart Images

Figure CN119943866A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery pole pieces, and in particular relates to a single-layer particle pole piece, a preparation method thereof and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in new energy vehicles, portable electronic devices, smart grids, energy storage and other fields due to their high operating voltage, high energy density and long cycle life. As the market demands for faster charging and discharging capabilities, longer battery life and higher energy density of lithium-ion batteries, it is of great significance to continue to improve the performance indicators of lithium-ion batteries.
[0003] The realization of high-performance lithium-ion batteries can be achieved by improving the performance of existing key materials or optimizing the structure and performance of existing key components. The characterization of these properties is mainly completed by using thick electrodes, and the results obtained are subject to many interference factors. Among them, the thickness, porosity, pore tortuosity and connectivity of the electrode will affect the ion transmission efficiency in the electrolyte, and the distribution of conductive carbon in the solid phase and the contact of particles will also affect the speed of electronic conduction. Moreover, since thick electrodes will have certain limitations on the electronic contact between the active material and the current collector and the diffusion of particles inside the electrode, the rate performance and cycle stability of the battery are reduced.
[0004] In order to eliminate the influence of other factors on key material properties, the existing technology generally uses thin film electrodes or single particle microscopic electrochemical characterization technology for characterization. Thin film electrodes deviate from the particle morphology of actual active materials, and their lattice orientation is more obvious than that of actual active materials. In addition, some materials cannot be made into thin films, which limits their application in the characterization of material kinetic properties. Single particle characterization technology can not only strip off the influence of inactive substances and pores, but also retain material defects, microstructures, grain boundaries and other characteristics, obtain the essential properties of actual materials (such as ion diffusion coefficient, exchange current, etc.), and measure active materials accurately and quickly. However, although single particle characterization technology can obtain accurate intrinsic kinetic behavior and parameters of materials, the solid phase diffusion process of lithium ions in single particle electrodes is closely related to the electrochemical active area (particle size), and the diffusion coefficient of the diffusion process determines the size of the reaction rate. It is one of the essential parameters for measuring material rate performance and conducting battery electrochemical simulation modeling. The larger the diffusion coefficient, the better the large current discharge capacity of the electrode, the higher the power density of the material, and the better the high rate performance. The particle size of active material particles in common commercial lithium-ion batteries ranges from hundreds of nanometers to tens of microns. In order to obtain a representative average diffusion coefficient of the material, it is necessary to measure particles of different sizes in the powder material multiple times, and pay attention to the particle size distribution of the particles in the original sample. For single-particle electrodes, how to obtain a representative diffusion coefficient in one go is a complex and arduous task. Furthermore, the precise processing of single particles (μm level) and the construction of electrochemical devices rely on high-precision operating tables, while the reliable measurement of tiny currents (nA level) requires precise testing equipment and shielding of environmental noise currents. Due to its difficult operation, precise and complex instruments, and weak current signals, it cannot be widely used. Single-layer particle electrode characterization technology came into being.
[0005] However, the existing single-layer particle electrode preparation technology still has various defects.
[0006] The existing method for preparing single-layer particle electrodes is usually to reduce the solid content of the slurry and change the solid material ratio on the basis of the traditional coating process to obtain single-layer particles. However, this method will cause particle sedimentation, resulting in uneven distribution of active particles or deviation from the actual battery ratio, and it is impossible to obtain accurate and effective data results. For example, patent CN114778633A provides a single-layer particle electrode and an electrochemical analysis method for electrochemical analysis, and a micro-electrode with single-layer particle deposition is prepared by a conventional coating process. In this patent, the solid content of the slurry is relatively low and the particle density coefficient is small. Active particles with larger particle size and higher density are very likely to settle in this system, resulting in uneven dispersion of active particles, and the electrochemical information of active particles with different particle size distributions cannot be fully presented.
[0007] Therefore, how to prepare a single-layer particle electrode with a uniform distribution of active particles of different sizes is the key to improving the rate performance and cycle stability of lithium-ion batteries. Furthermore, developing a manufacturing method for single-layer particle electrodes that can be applied on a large scale while taking into account the advantages of single-layer particle electrodes such as accuracy and speed is a technical problem that needs to be solved urgently in the field of battery research. Summary of the invention
[0008] In view of this, the present invention aims to provide a single-layer particle electrode sheet, a preparation method thereof and a lithium-ion battery, so as to solve the technical problem that the electrode electrode sheet prepared in the prior art is difficult to use for battery performance characterization to obtain accurate and comprehensive electrochemical performance parameters because the active particles are prone to sedimentation or deviate from the actual battery ratio.
[0009] In a first aspect, the present invention provides a method for preparing a single-layer particle electrode, the method comprising:
[0010] A primer slurry is coated on the current collector, wherein the primer slurry includes a conductive agent, a binder, a first solvent and a second solvent, wherein the first solvent and the second solvent satisfy the following conditions: the first solvent and the second solvent are mutually soluble, and the saturated vapor pressure of the first solvent is less than the saturated vapor pressure of the second solvent and less than 30 kPa; and 20° C. is less than the boiling point of the second solvent and less than 80% of the boiling point of the first solvent;
[0011] Active particles are spread on the current collector coated with the primer slurry.
[0012] Furthermore, the purpose of the first solvent and the second solvent satisfying "the saturated vapor pressure of the first solvent < the saturated vapor pressure of the second solvent < 30 kPa; 20°C < the boiling point of the second solvent < 80% of the boiling point of the first solvent" is to reduce the overall saturated vapor pressure of the slurry and to control the adhesion of the primer slurry by controlling the amount and ratio of the first solvent and the second solvent added.
[0013] Furthermore, the mass ratio of the conductive agent to the binder is (0.2-3):1, the mass proportion of the conductive agent and the binder in the primer slurry is 2%-20% in the overall slurry, and the mass proportion of the active particles relative to the total mass of the active particles, the conductive agent and the binder is 60%-97%.
[0014] Furthermore, the conductive agent is selected from at least one of conductive carbon black (SP), single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, silver nanowires or carbon nanofibers; and / or the binder is selected from at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA) or polyvinyl alcohol (PVA); and / or the current collector is selected from aluminum foil or copper foil.
[0015] Further, the active particles are selected from at least one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium cobalt oxide, graphite, lithium titanate or lithium manganese oxide; preferably, the active particles are selected from nickel cobalt manganese ternary material particles with D90≤33μm, D90≤10μm, D90≤5μm, lithium titanate particles with D90≤900nm, lithium manganese oxide particles with D90≤30μm, lithium iron phosphate particles with D90≤7μm, lithium cobalt oxide particles with D90≤32μm or graphite particles with D90≤26μm, D90≤38μm, D90≤45μm.
[0016] Furthermore, the preparation process of the primer slurry includes: pre-dissolving the binder into the first solvent, then adding the conductive agent and mixing, and finally adding the second solvent to the system and mixing. By adjusting the ratio of the first solvent to the second solvent, the adhesion of the primer film can be controlled, thereby achieving the adjustment of the surface density of the active particles.
[0017] Preferably, the binder is pre-dissolved in part of the first solvent, and then the conductive agent is added thereto and mixed, and finally the second solvent and the remaining first solvent are mixed and added to the system and mixed, and the part of the first solvent accounts for 8%-100% of the total mass of the first solvent. The first solvent is preferably added in two parts for the following main purposes: first, to further improve the compatibility of the second solvent with the entire system, and second, the "remaining first solvent" can be used to flexibly control the solid content of the slurry, and the second solvent itself is a solvent with good compatibility. By controlling the ratio of the first solvent to the second solvent, the second solvent will evaporate during the coating process, and basically only the first solvent will remain in the primer film. The adhesion of the primer film is related to the amount of the first solvent, and the particle attachment effect is related to the adhesion. The stronger the adhesion, the higher the particle attachment density.
[0018] Furthermore, the mass ratio of the first solvent to the second solvent is 1:(1-3), and the amount and ratio of the first solvent and the second solvent added are controlled to regulate the viscosity of the primer slurry, thereby regulating the final particle surface density of the electrode; the first solvent is selected from N-methylpyrrolidone (NMP) and / or water, and the second solvent is selected from at least one of ethyl acetate, ethyl butyl ether, isopropyl acetate (IPAC), tetrahydrofuran, ethanol or acetone.
[0019] Apply the primer slurry on the current collector by spin coating or coating: take a certain amount of slurry and spin coat or coat it on the current collector, and control the relevant parameters to adjust the film thickness; in addition, the film thickness can be adjusted by adjusting the solid content of the primer slurry. The primer film thickness can be adjusted according to the actual application requirements, and the preferred range is ≤20μm. Since the film layer after spin coating is extremely thin, the second solvent will basically evaporate during the spin coating process. It can be left to stand for a period of time before proceeding to the next step to ensure that the second solvent is completely evaporated.
[0020] Furthermore, the preparation method further comprises: cold pressing, dust removal and drying after spreading the active particles.
[0021] Furthermore, the pressure applied in the cold pressing step is preferably in the range of 0-5000Pa, and the drying procedure is baking at a temperature of 50-90°C for more than 1h; vacuum dust removal is used for dust removal. On the one hand, the dust removal step is to remove the active particles that are not in contact with the primer slurry layer to prevent the binder and solvent of the slurry from spreading upward to the upper layer of active particle powder during the drying process, causing agglomeration between the active particles, and excess active particles are not easy to fall off; on the other hand, it is to remove the active particles on the dried electrode that are not tightly connected to the primer slurry layer to prevent interference with the test results.
[0022] Furthermore, the method also includes: electrostatically spraying a layer of electrospray slurry on the active particles to increase conductivity, and then drying to obtain a pole piece with a single layer of dispersed particles.
[0023] Furthermore, the preparation process of the electrospray slurry includes: dissolving the binder into the first solvent, and then adding the conductive agent thereto and mixing them evenly.
[0024] In the second aspect, the present invention provides a single-layer particle electrode, wherein the single-layer particle electrode comprises at least a current collector layer, a primer slurry layer (inner layer) and an active single-layer particle layer (middle layer) arranged in sequence, and the active particle layer has a film thickness of ≤ 100% of the active particle D max (maximum size of active particles).
[0025] Preferably, an electrospray layer is also provided above the active particle layer. The electrospray layer is arranged above the active particle layer. Both the primer slurry and the electrospray layer contain conductive agents, which can more significantly improve the electron transmission effect of the active particles. At this time, the single-layer particle electrode includes a four-layer structure, namely: a current collector layer, a primer slurry layer (inner layer), an active single-layer particle layer (middle layer) and an electrospray layer (outer layer).
[0026] In a third aspect, the present invention provides a lithium-ion battery comprising the above-mentioned single-layer particle electrode.
[0027] The single-layer particle electrode, preparation method thereof and lithium-ion battery provided by the present invention have the following beneficial effects:
[0028] (1) A single layer of active particles of different sizes are evenly dispersed on the surface of the electrode plate, which is helpful for obtaining accurate and comprehensive electrochemical data; the gaps between the lateral particles on the single-layer particle plate can reserve space for particle expansion, and there is no expansion pressure given by the upper and lower particles in the vertical direction; due to the single-layer particle dispersion, the ion transmission efficiency in the electrolyte during the electrochemical test will not be affected by the electrode thickness porosity, pore tortuosity and connectivity; in addition, when pressure is applied in the active particle dispersion step, the primer slurry will be partially displaced, so that the active particles are in direct contact with the current collector or in closer contact with the conductive agent, which is conducive to improving the electron transmission effect;
[0029] (2) A single-layer particle dispersion effect with adjustable active particle surface density is achieved; the representative average diffusion coefficient of active particles with different particle size distributions can be obtained at one time, which can better perform battery simulation and design;
[0030] (3) The thickness of the primer film and the surface density of active particles can be flexibly adjusted to meet the design and characterization of various electrodes; the surface density of active particles can be adjusted by controlling the adhesion of the primer film and the applied pressure to achieve different single-layer particle dispersion effects;
[0031] (4) The operation steps are simple and do not require the use of sophisticated instruments;
[0032] (5) The single-layer particle electrode can be applied to the fields of fast charging and high-rate batteries and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a topographical image of the electrode sheet with a three-layer structure in Example 1;
[0034] Figure 2 This is a morphology diagram of the electrode sheet with a four-layer structure in Example 2;
[0035] Figure 3 This is the morphology of the three-layer electrode sheet of comparative example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0037] Example 1 (SP / PVDF=2.5, IPAC / NMP=1.5)
[0038] The preparation method of the single-layer particle electrode is as follows:
[0039] (1) Primer slurry preparation and coating:
[0040] First, add 100g NMP to 5g PVDF, and use a mixer to mix at 1500rpm for 5min until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 1.79g conductive agent SP to 15g PVDF-NMP and premix at 1500rpm for 5min, then mix 4.71g NMP with 28.5g IPAC, and then add it to the premixed liquid, and mix at 1500rpm for 5min with a mixer, and repeat the mixing 5 times to obtain the primer slurry.
[0041] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0042] (2) Active particle dispersion:
[0043] After spin coating, let it stand for 10 minutes. After the IPAC is basically volatilized, use a fully automatic powder spreading machine to sprinkle active particles of ternary NCM particles (D90≤33μm) on the surface of the primer film, apply a force of 500g (average pressure of 500Pa) on the active particles, and use vacuum dust removal to remove the active particles that are not in direct contact with the primer film surface. Then use 80℃ oven to dry for 60 minutes, and use vacuum dust removal again to remove the active particles that are not in close contact with the primer film surface.
[0044] The electrode sheet with three layers is obtained. The morphology of the electrode sheet is shown in the figure Figure 1 As shown, the three-layer structure includes: a current collector layer, a primer slurry layer (inner layer) and an active single-layer particle layer (middle layer), which can be applied to electrochemical performance testing.
[0045] Example 2
[0046] The preparation method of the single-layer particle electrode is as follows:
[0047] (1) Primer slurry preparation and coating:
[0048] First, add 100gNMP to 5g PVDF and mix it at 1500rpm for 5min until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 1.79g conductive agent SP to 15g PVDF-NMP and premix it at 1500rpm for 5min, then mix 4.71gNMP with 28.5g IPAC, and then add it to the premixed liquid, mix it at 1500rpm for 5min, and repeat the mixing 5 times to obtain the primer slurry.
[0049] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0050] (2) Active particle dispersion:
[0051] After spin coating, let it stand for 10 minutes. After the IPAC is basically volatilized, use a fully automatic powder spreading machine to sprinkle active particles of ternary NCM particles (D90≤33μm) on the surface of the primer film, apply a force of 500g (average pressure of 500Pa) on the active particles, and use vacuum dust removal to remove the active particles that are not in direct contact with the primer film surface. Then use 80℃ oven to dry for 60 minutes, and use vacuum dust removal again to remove the active particles that are not in close contact with the primer film surface.
[0052] (3) Upper layer electrospray slurry configuration:
[0053] The configuration of the electrospray slurry is the same as that of the primer slurry, with the only difference being that the IPAC in the primer slurry is completely replaced by NMP. A layer of electrospray slurry is electrostatically sprayed on the active particles dispersed in a single layer of particles, and then dried in an oven at 80°C for 2 hours to obtain a single-layer particle electrode.
[0054] The above-mentioned single-layer particle electrode is a four-layer structure, and the electrode electrode morphology is shown in the figure Figure 2 As shown, the four-layer structure includes: a current collector layer, a primer slurry layer (inner layer), an active single-layer particle layer (middle layer) and an electrospray layer (outer layer), which can be applied to electrochemical performance testing.
[0055] Example 3 (graphite-water system)
[0056] The difference from Example 1 is:
[0057] Step (1) is replaced by:
[0058] First, add 97g H2O to 3g CMC, and use a mixer to mix at 1500rpm for 5min until there is no obvious solid particles, which is recorded as CMC-H2O. Add 0.38g conductive agent SP to 15g CMC-H2O and premix at 1500rpm for 5min, then mix 5.45g H2O with 20.68g acetone, and then add it to the premixed liquid, and mix at 1500rpm for 5min, repeat the mixing 5 times, then add 1.35g SBR solution with a solid content of 50%, and then mix twice to obtain the primer slurry.
[0059] Fix a 10cm*10cm copper foil on a glass substrate, add 3ml of primer slurry to the center of the copper foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0060] The active particles in step (2) are replaced with graphite particles (D90≤38 μm), and the remaining steps are the same as in Example 1.
[0061] Example 4
[0062] The difference from Example 1 is that the second solvent "IPAC" is replaced by "tetrahydrofuran", and the remaining steps are the same as Example 1.
[0063] Example 5
[0064] The difference from Example 1 is that the conductive agent "SP" is replaced by "graphene", and the remaining steps are the same as Example 1.
[0065] Example 6
[0066] The difference from Example 1 is that the active particles NCM are replaced by LTO (D90≤900nm), and the remaining steps are the same as Example 1.
[0067] Example 7
[0068] The difference from Example 1 is that the active particles NCM are replaced by LFP (D90≤7μm), and the remaining steps are the same as Example 1.
[0069] Example 8 (SP / PVDF=0.75)
[0070] The difference from Example 1 is:
[0071] Step (1) is replaced by:
[0072] First, add 40gNMP to 5g PVDF, and use a mixer to mix at 1500rpm for 5min until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 1.25g conductive agent SP to 15g PVDF-NMP and premix at 1500rpm for 5min, then mix 8.83g NMP with 33.25g IPAC, and then add it to the premixed liquid, and mix at 1500rpm for 5min with a mixer, and repeat the mixing 5 times to obtain the primer slurry.
[0073] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0074] The remaining steps are the same as those in Example 1.
[0075] Example 9 (IPAC / NMP=3)
[0076] The difference between the steps and Example 1 is:
[0077] Step (1) is replaced by:
[0078] First, add 40gNMP to 5g PVDF, and use a mixer to mix at 1500rpm for 5min until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 4.17g conductive agent SP to 15g PVDF-NMP and premix at 1500rpm for 5min, then mix 14.38gNMP with 83.13g IPAC, and then add it to the premixed liquid, and mix at 1500rpm for 5min with a mixer, and repeat the mixing 5 times to obtain the primer slurry.
[0079] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0080] The remaining steps are the same as those in Example 1.
[0081] Example 10 (IPAC / NMP=1)
[0082] The difference from Example 1 is:
[0083] Step (1) is replaced by:
[0084] First, add 100g NMP to 5g PVDF, and use a mixer to mix at 1500rpm for 5min until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 1.79g conductive agent SP to 15g PVDF-NMP and premix at 1500rpm for 5min, then mix 9.46g NMP with 23.75g IPAC, and then add it to the premixed liquid, and mix at 1500rpm for 5min with a mixer, and repeat the mixing 5 times to obtain the primer slurry.
[0085] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0086] The remaining steps are the same as those in Example 1.
[0087] Embodiment 11
[0088] The difference from Example 1 is that the applied pressure of 500 g in step (2) is changed to 2000 g. The specific steps are as follows:
[0089] After spin coating, let it stand for 10 minutes. After the IPAC is basically volatilized, use a fully automatic powder spreading machine to sprinkle active particles of ternary NCM particles (D90≤33μm) on the surface of the primer film, apply a force of 2000g (average pressure of 2000Pa) on the active particles, and use vacuum dust removal to remove the active particles that are not in direct contact with the primer film surface. Then use 80℃ oven to dry for 60 minutes, and use vacuum dust removal again to remove the active particles that are not in close contact with the primer film surface.
[0090] The remaining steps are the same as those in Example 1.
[0091] Comparative Example 1
[0092] Based on Example 1, the two solvents, NMP and IPAC, were replaced by only one solvent, NMP. The specific preparation method is as follows:
[0093] (1) Primer slurry preparation and coating:
[0094] First, add 100g NMP to 5g PVDF and use a mixer to mix for 5min at 1500rpm until there are no obvious solid particles, which is recorded as PVDF-NMP. Add 1.79g conductive agent SP to 15g PVDF-NMP and premix at 1500rpm for 5min, then add 33.21g NMP to the premixed liquid and mix at 1500rpm for 5min, and repeat the mixing 5 times to obtain the primer slurry.
[0095] Fix a 10cm*10cm aluminum foil on a glass substrate, add 3ml of primer slurry to the center of the aluminum foil, and set the spin coating parameters to 500rpm 10s / 2000rpm 30s / 500m / s 2 Acceleration for spin coating.
[0096] (2) Active particle dispersion:
[0097] After spin coating, active ternary NCM particles (D90≤33μm) were sprinkled on the surface of the primer film using an automatic powder sprinkler, a force of 500g (average pressure of 500Pa) was applied to the active particles, and the active particles that were not in direct contact with the primer film surface were removed by vacuum dust removal. The samples were then dried in an oven at 80°C for 60 minutes, and the active particles that were not in close contact with the primer film surface were removed by vacuum dust removal again.
[0098] Electrode sheet morphology Figure 3 As shown, it can be seen from the morphology diagram that the active particles on the electrode plate prepared in Comparative Example 1 are obviously stacked.
[0099] Comparative Example 2
[0100] Based on Example 1, all components were mixed in one step, and the preparation method was as follows:
[0101] 15g PVDF-NMP, 1.79g conductive agent SP, 80.83g active particle ternary NCM particles (D90≤33μm), 4.71g NMP and 28.5g IPAC were mixed in one step, and mixed at 1500rpm for 5min using a slurry mixer, and the slurry was obtained after repeated mixing 5 times. After the slurry was left to stand for 10min, obvious precipitation appeared at the bottom, which was not suitable for coating.
[0102] Test method: Define film thickness ≤ D max (maximum size of active particles) is considered as a single-layer particle, D max It can be determined by SEM images, and the film thickness can be determined by a step profiler or ultra-depth of field microscope. The test results are listed in Table 1.
[0103] Table 1
[0104]
[0105] Comparing Example 1 and Comparative Example 1, it can be seen from the data in the table that using two solvents in the process of preparing the primer slurry and satisfying "the saturated vapor pressure of the first solvent < the saturated vapor pressure of the second solvent < 30kPa; 20°C < the boiling point of the second solvent < 80% of the boiling point of the first solvent" can prepare a single-layer particle electrode, and the electrochemical performance parameters of the electrode sheet can be obtained by using the single-layer particle characterization technology; if only a single solvent is used, the active particles on the coated film will be in a stacked state, which cannot be used for battery performance characterization to obtain accurate electrochemical performance parameters. Comparing Example 1 and Comparative Example 2, it can be seen that the conventional one-step mixed coating process will cause the active particles in the slurry to settle and disperse unevenly, and cannot fully present the electrochemical information of active particles with different particle size distributions, which is not conducive to electrochemical performance characterization.
[0106] Although the embodiments of the present invention have been described in conjunction with the accompanying drawings, those skilled in the art may make various modifications and variations without departing from the spirit and scope of the present invention, and such modifications and variations are all within the scope defined by the present invention.
Claims
1. A method for preparing a single-layer particle electrode, characterized in that: The method includes: A primer slurry is coated on the current collector, wherein the primer slurry includes a conductive agent, a binder, a first solvent and a second solvent, wherein the first solvent and the second solvent satisfy the following conditions: the first solvent and the second solvent are mutually soluble, the saturated vapor pressure of the first solvent is less than the saturated vapor pressure of the second solvent and less than 30 kPa; and 20° C. is less than the boiling point of the second solvent and less than 80% of the boiling point of the first solvent; Active particles are spread on the current collector coated with the primer slurry.
2. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The mass ratio of the conductive agent to the binder is (0.2-3):1, the mass proportion of the conductive agent and the binder in the primer slurry is 2%-20% in the overall slurry, and the mass proportion of the active particles relative to the total mass of the active particles, the conductive agent and the binder is 60%-97%.
3. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The conductive agent is selected from at least one of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, silver nanowires or carbon nanofibers; and / or the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyacrylic acid or polyvinyl alcohol; and / or the current collector is selected from aluminum foil or copper foil.
4. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The mass ratio of the first solvent to the second solvent is 1:(1-3), the first solvent is selected from N-methylpyrrolidone and / or water, and the second solvent is selected from at least one of ethyl acetate, ethyl butyl ether, isopropyl acetate, tetrahydrofuran, ethanol or acetone.
5. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The active particles are selected from at least one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium cobalt oxide, graphite, lithium titanate or lithium manganese oxide.
6. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The preparation process of the primer slurry includes: pre-dissolving the binder into a first solvent, adding the conductive agent thereto and mixing evenly, and finally adding the second solvent into the system and mixing evenly.
7. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The method further comprises: cold pressing, dust removal and drying after spreading the active particles.
8. The method for preparing a single-layer particle electrode according to claim 1, characterized in that: The method also includes: electrostatically spraying a layer of electrospray slurry on the active particles.
9. The method for preparing a single-layer particle electrode according to claim 8, characterized in that: The preparation process of the electrospray slurry includes: dissolving a binder into a first solvent, and then adding a conductive agent therein and mixing evenly.
10. A single-layer particle electrode, characterized in that: The single-layer particle electrode is prepared by the preparation method of any one of claims 1-9.
11. The single-layer particle electrode according to claim 10, characterized in that: The single-layer particle electrode comprises at least a three-layer structure of a current collector layer, a slurry layer and an active particle layer arranged in sequence, and the film thickness of the active particle layer is ≤ the maximum size of the active particles.
12. The single-layer particle electrode according to claim 10, characterized in that: The single-layer particle electrode also includes an electrospray layer, and the electrospray layer is arranged above the active particle layer.
13. A lithium ion battery, characterized in that: It includes a single-layer particle electrode produced by any preparation method described in claims 1-9 or a single-layer particle electrode described in any one of claims 10-12.